Digital storytelling as a didactic sequence for promoting the speaking skill in 10th graders for a public school (2022)
This writing paper aimed at designing a didactic sequence using digital storytelling in a foreign language classroom which focused on the development of the speaking skill in media education. This didactic sequence used qualitative research which sought for the study of the participants in their environment. The targeted population for this project is secondary education students which will be involved in a series of workshops for the creation of virtual narrative stories in their foreign language. This didactic sequence has as the main objectives, in the first hand that students will be able to tell a virtual narrative story in English and on the other to be a model for future teachers to integrate technology in language teaching. The results expected after the design of this didactic sequence will be that students gain knowledge in the creation of this text typology which is narrative stories and the strengthening of the speaking skills to achieve a higher level of English proficiency